MULTIPARAMETER ADAPTIVE CONTROL SYSTEM OF GRAIN COMBINE - Dmitry Y. Parshin; Denis G. Shevchuk (Advanced Engineering Research)
The basic exposure for the grain combine, and its effect on the motion pattern and combining are considered. The technique and algorithm of the multiparameter adaptive control of grain combine are proposed. The structure and adaptive control system elements interconnection of grain combine are observed.